Importance of bone marrow examination in cases of pancytopenia: A morphological study in a tertiary care center - Deepshikha Verma; Ranjan Yadav; Rajnikant Ahirwar; Pratibha Meena (Asian Journal of Medical Sciences, 2024)
Background: Anemia, leukopenia, and thrombocytopenia are all combined as pancytopenia. It could be a symptom of many diseases that directly or indirectly impact the bone marrow. The cause of pancytopenia, however, differs depending on the location. An essential step in determining the cause of pancytopenia is bone marrow aspiration (BMA).